Anti-vaccine COVID-19 narratives: A critical textual analysis of American and Indonesian online news - Imelsa Dwi Veronika; Agwin Degaf (Studies in English Language and Education)
This study utilized Critical Discourse Analysis (CDA), grounded in Van Dijk’s framework to investigate how online news articles from American and Indonesian outlets portrayed anti-vaccine views related to COVID-19. Through systematic online searches, the research examined the data through the lenses of macrostructure, superstructure, and microstructure. Eight articles were selected for this study: four from American sources and four from Indonesian sources. The selected articles were published during specific periods: February 2022 to February 2023 for the U.S., and January 2021 to January 2022 for Indonesia. These articles, ranging from 500 to 1500 words, focused on ‘Anti-Vaccine COVID-19’ topics. The findings revealed distinct thematic differences. The macrostructure analysis showed that American articles highlighted distrust in specific vaccines and opposition to mandates, fostering skepticism, while Indonesian articles examined a wider range of cultural, religious, and personal factors influencing vaccine hesitancy, including anti-vaccine sentiments among expatriates and athletes. The superstructure analysis indicated that American reports emphasized controversy, whereas Indonesian reports explored motivations more deeply. Additionally, linguistic choices in the microstructure influenced portrayals, with American articles using dysphemism and active voice to emphasize danger, while Indonesian articles employed strong language to convey diverse perspectives. Despite its emphasis on textual analysis, this study offered significant insights into the sophisticated discussions of anti-vaccine sentiments in the context of the COVID-19 pandemic, as reflected in American and Indonesian online news.